Dramatization of stories for the practice of moral values at the initial level, Chaglla - 2019 - Sotil-Cortavarría, Wilfredo A. (2020)
The objective of scientific research is to disclose its results in a printed form, they are essential, since they indicate what is expected of the research and define the way in which the result will be achieved, raise it, is to determine the goal to which it is aspired get there by exploring. And all this is reflected in the broadcasts made, and which are presented in a documentary way, all research that is presented is documentary and published. The purpose of this article is to identify patterns of formulation of the objectives, the sections where they are presented and support for science, and through this, to show students that they can also prepare manuscripts that have the possibility of being accepted for their publication and to be perfectly understood when they are published. Therefore, this article will gain its importance, insofar as it is taken as a guide by those professionals who wish to publish their studies in different national and international journals.